The influence of algae habitat refuge complexity on juvenile fish growth, condition, and survival under the presence or absence of predators - Hilmar Hinz; Maria del Mar Gil; Paula Anglada; José Maria Disdier; Olga Reñones; Gaetano Catanese; Julia Castro-Fernández; Antoni Sureda; Amalia Grau; Adam Gouraguine; Joan Moranta (Marine Environmental Research, 2026)

Vascular Endothelial Growth Factor-A and Collateral Circulation in Patients with Acute Ischemic Stroke due to Intracranial Large Vessel Occlusion - Ana Aguilera-Simón; Marina Guasch-Jiménez; Francisco Moniche; Núria Puig; Blanca Pardo-Galiana; Sònia Benítez; Maria del Mar Freijo; Rebeca Marín; Alain Luna; Cristina Gallego-Fabrega; Isabel Fernández-Pérez; Garbiñe Ezcurra-Díaz; et al. (Translational Stroke Research, 2026)

Presence and Potential Effect of Microplastics Associated with Anthropic Activity in Two Benthic Fishes Serranus scriba and Lithognathus mormyrus - Amanda Cohen-Sánchez; Juan Alejandro Sanz; Montserrat Compa; Maria Magdalena Quetglas-Llabrés; Maria del Mar Ribas-Taberner; Lorenzo Gil; Silvia Tejada; Samuel Pinya; Antoni Sureda (Fishes, 2025)
Plastic pollution poses a massive problem to the environment, particularly seas and oceans. Microplastics (MPs) ingestion by marine species can generate many adverse effects, including causing oxidative stress. This study evaluated the effects of anthropic activity-related MP presence in two coastal fish species—Serranus scriba (more related to rocky bottoms) and Lithognathus mormyrus (more related to sandy bottoms)—in two areas of Mallorca Island (Western Mediterranean) with varying anthropic pressures with similar mixed rocky/sandy bottoms. A total of eight fish samples per species and per area (total n = 32), as well as three water samples (500 mL each) and three sediment samples per area, were collected and analyzed. The results showed that despite plastic presence in both areas, the area with higher tourism affluence was also the most polluted. Fourier transform infrared spectroscopy analysis confirmed that the majority of recovered polymers were polyethylene and polypropylene. The pattern of MPs presence was reflected in the biomarker analysis, which showed higher values of antioxidants, namely catalase (CAT) and superoxide dismutase (SOD); detoxification, namely glutathione s-transferase (GST); and inflammation, namely myeloperoxidase (MPO)—enzymes in the gastrointestinal tract of fish from the more polluted area. However, no statistical differences were found for malondialdehyde (MDA) as a marker of lipid peroxidation. As for differences between species, S. scriba presented a higher presence of MPs and measured biomarkers than in L. Mormyrus, suggesting higher exposure. In conclusion, these results showed that increased anthropic activity is associated with a higher presence of MPs which, in turn, induces an adaptative response in exposed fish. Moreover, species living in the same area could be differentially affected by MPs, which is probably associated with different behavioural and feeding habits.

Static nets in motion: Evaluating seabed interactions of trammel nets deployed in two Mediterranean artisanal fisheries - Maria del Mar Gil; José María Disdier-Gómez; Gaetano Catanese; Silvia de Juan; Hilmar Hinz (Fisheries Research, 2025)

Macrophyte complexity influences habitat choices of juvenile fish - Hilmar Hinz; Paula Anglada; Alberto Gayá Vilar; Olga Reñones; Gaetano Catanese; Julia Castro-Fernández; Maria del Mar Gil; Amalia Grau; Joan Moranta (Marine Biology, 2023)
The nursery function of littoral habitats for juvenile fish is widely recognized, but data on the specific habitat features that contribute to this function is sparse for many species, in part related to the difficulty of studying juvenile fish in their natural environment. However, this information is required to understand the potential risks of environmental change to the nursery functions of habitats. In this context, the habitat choice behaviour, with respect to differences in structural features, was evaluated for three Mediterranean littoral fish species known to be associated to macrophytes as juveniles. The overarching aim of this experiment was to determine if juveniles actively choose between different macrophyte configurations of varying complexity and height. Juveniles were exposed simultaneously to multiple visual habitat stimuli within an experimental choice arena, and their swimming behaviour was tracked by video recordings to determine the amount of time they spent near each habitat configuration. All three species showed a clear association in their occupancy towards more complex habitat configurations demonstrating that juveniles distinguished and actively selected habitats using visual cues. Subtle differences in species' affinity for complex habitats allowed us to appraise their potential vulnerabilities to habitat loss in the Mediterranean under environmental change scenarios. Furthermore, the results of this study provided evidence that differences in juvenile distribution between habitats found in previous observational studies may indeed be caused by active habitat selection, as well as through differential survivorship rates.

Multisite assessment of the impact of a prenatal testing educational App on patient knowledge and preparedness for prenatal testing decision making - Patricia Winters; Kirsten J. Curnow; Alexandra Benachi; Maria Mar Gil; Belen Santacruz; Miyuki Nishiyama; Fuyuki Hasegawa; Haruhiko Sago (Journal of Community Genetics, 2022)
In this study, we wanted to assess the impact of the use of a patient educational app on patient knowledge about noninvasive prenatal testing (NIPT) and preparedness for prenatal screening decision-making. A randomized control study was carried out at three international sites between January 2019 and October 2020. Study participants completed a pre-consultation survey and post-consultation survey to assess knowledge, satisfaction, and preparedness for prenatal screening consultation. Providers completed a post-consultation survey. In the control arm, the pre-consultation survey was completed prior to consultation with their prenatal care provider. In the intervention arm, the pre-consultation survey was completed after using the app but prior to consultation with their prenatal care provider. Mean knowledge scores in the 203 participants using the app were significantly higher pre-consultation ( p < 0.001) and post-consultation ( p < 0.005) than those not using the app. Higher pre-consultation knowledge scores in the intervention group were observed at all sites. Most (86%) app users stated they were “Satisfied” or “Very Satisfied” with it as a tool. Providers rated the intervention group as more prepared than controls ( p = 0.027); provider assessment of knowledge was not significantly different ( p = 0.073). This study shows that clinical implementation of a patient educational app in a real-world setting was feasible, acceptable to pregnant people, and positively impacted patient knowledge.